indonesia Korelasi pemahaman etika, sains dan teknologi dapat meningkatkan kehidupan sosial dan kemanusiaan - Rahma, Nafilah Azaria; Nurrohmah, Nova Budi; Ridho, M.; mahardika, I ketut; sari, Erna; Handono, Sri (Jurnal Ilmiah Wahana Pendidikan, 2024)
Science and ethics are two interrelated concepts in the development of science and technology. Knowledge of scientific ethics is a reference when responding to the increasingly rapid development of science in the era of society. Scientific ethics is closely related to human responsibility, not only in the application of scientific and technological concepts, but also in predicting possible natural and social changes. By using the summarize research method, this article aims to examine regulations for the use of technology and science for the development of technological science, as well as directing technological science in a direction that is in accordance with the norms that apply in society